CerminanFilosofi Batak Toba “Dalihan Natolu” Terhadap Nilai-Nilai Luhur Bangsa Indonesia - Mangudur, Theovanni Indah; Waruwu, Lina Yanti; Sari, Henny; Putriyansyah, Wilda; Sofyanti, Dina Febri; Hasibuan, Sarmila; Ivanna, Julia (Journal of Law & Policy Review, 2023)
This article aims to analyze the philosophical views of the Batak Toba “Dalihan Natolu” towards the noble values of the nation. The problem is focused on the position and role of the values contained in the Dalihan Natolu and it’s relation to the noble values of the nation. In order to approach this problem, a theoretical reference is used Pasaribu in the Armawi (2008) Batak Toba people have a level of obedience and obedience in social relations as regulated in the cultural structure of the Dalihan Natolu so that it is perceived as one of the ways or methods in achieving life.  Dalihan Natolu is a cultural value, the prime idea of its creator which is the source or orientation of the attitudes and behavior of the Batak tribe in their lives in social and cultural relationship. The data is collected through literature review of various writings search on the internet and analyzed qualitatively. This study concludes that Dalihan Natolu is a philosophy that contains noble cultural values in the life of the Batak Toba people, in the implementation of the Batak Toba customs,it is inseparable from the Dalihan Natolu philosophy which regulates the customary life of the Batak Toba community. Dalihan Natolu values are not only as values in the Barak Toba traditional system, but also in line with the noble values adopted by the Indonesian people.